2019
DOI: 10.3168/jds.2018-15752
|View full text |Cite
|
Sign up to set email alerts
|

Suitability of somatic cell count, electrical conductivity, and lactate dehydrogenase activity in foremilk before versus after alveolar milk ejection for mastitis detection

Abstract: Mastitis is responsible for substantial economic loss and significant animal welfare concerns for the dairy industry. Sensors that measure electrical conductivity (EC) and enzyme concentrations of lactate dehydrogenase (LDH) are presently used for automatic detection of mastitis. However, EC is not sensitive enough to detect mastitis, and the ability of LDH activity to identify mastitis caused by different pathogens is a potential option that needs to be investigated. This study was conducted to test the follo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 53 publications
6
25
0
Order By: Relevance
“…The obtained overall means for fat and protein percentages estimated from the foremilk (2.80%, 3.51%) were close to those reported by Khatun et al (2019), who found that the means of fat and protein percentages were 2.83% and 3.41%, respectively, using foremilk samples from Holstein-Friesian cows in Australia. Most of the studies on raw milk composition of Holstein cows in Egypt reported that milk fat percentage ranged from 2.97% to 3.74% (Zeinhom et al, 2016;Nasr & El-Tarabany, 2017).…”
Section: Fat and Protein Percentagessupporting
confidence: 86%
“…The obtained overall means for fat and protein percentages estimated from the foremilk (2.80%, 3.51%) were close to those reported by Khatun et al (2019), who found that the means of fat and protein percentages were 2.83% and 3.41%, respectively, using foremilk samples from Holstein-Friesian cows in Australia. Most of the studies on raw milk composition of Holstein cows in Egypt reported that milk fat percentage ranged from 2.97% to 3.74% (Zeinhom et al, 2016;Nasr & El-Tarabany, 2017).…”
Section: Fat and Protein Percentagessupporting
confidence: 86%
“…Electrical conductivity (EC) and enzymatic concentrations of lactate dehydrogenase (LDH) have been used as indicators to detect mastitis [ 96 , 97 ]. Recent works have shown the potential of using sensors for automatic measurement of EC and LDH; however, the results showed that there is still a need for further research in this field [ 95 ].…”
Section: Welfare Of Dairy Cows and Precision Livestock Farmingmentioning
confidence: 99%
“…Biomarkers show great promise, but a word of caution is required. The physiological principle underpinning the use of milk conductivity for mastitis detection was first shown in the mid-70s (Linzell and Peaker, 1975), and it took 30 years or more for the principle to be put into commercial practice and some studies still question the validity of the approach (Khatun et al, 2019).…”
Section: Biomarkersmentioning
confidence: 99%
“…Sensor modalities in use include somatic cell counting (SCC), lactate dehydrogenase concentration and milk conductivity. We have just mentioned scientific concerns about some aspects of this (Khatun et al, 2019) but is there any industry-level indication of significant problems? Frössling Knight et al (2017) documented AMS uptake in Sweden between 2008 and 2011 and showed that AMS was associated with increased mastitis risk (elevated SCC), but that this effect decreased over time and was less important than other factors such as time of year.…”
Section: Sensors For Wellbeingmentioning
confidence: 99%